3-bromo-1-hydroxy-9,10-anthraquinone (BHAQ) inhibits growth and migration of the human breast cancer cell lines MCF-7 and MDA-MB231 - Abu, Nadiah; Akhtar, Muhammad Nadeem; Ho, Wan Yong; Yeap, Swee Keong; Mohammed Alitheen, Noorjahan Banu (MDPI, 2013)
Breast cancer is becoming more prominent in women today. As of now, there are no effective treatments in treating metastatic breast cancer. We have tested the cytotoxic and anti-migration effects of BHAQ, a synthesized anthraquinone, on two breast cancer cell lines, MCF-7 and MDA-MB231. Anthraquinones are an interesting class of molecules that display a wide spectrum of biological applications, including anticancer properties. Cellular inhibition was tested through a MTT assay, double acridine orange/propidium iodide staining and FACS cell cycle analysis. Inhibition of migration was tested by the wound healing method, and migration through a Boyden chamber. BHAQ was cytotoxic towards both cell lines in a dose dependent and possibly cell-dependent manner. Additionally, BHAQ also inhibited the migration of the highly metastatic MDA-MB231 cell line.